Guided circumferential waves in layered poroelastic cylinders - Shah, Ahmed S.; Apsar, G. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper investigates the propagation of time harmonic circumferential waves in a two-dimensional hollow poroelastic cylinder with an inner shaft (shaft-bearing assembly). The hollow poroelastic cylinder and inner shaft are assumed to be infinite in axial direction. The outer surface of the cylinder is stress free and at the interface, between the inner shaft and the outer cylinder, it is assumed to be free sliding and the interfacial shear stresses are zero, also the normal stress and radial displacements are continuous.
Keywords: Biot`s theory; poroelastic layered cylinder; circumferential waves; shaft-bearing assembly; borepiston assembly; permeable surface; impermeable surface; wave number; frequency